ByzRev 03.2021.012: Franco Montanari (Hrsg.), History of Ancient Greek Scholarship.: From the Beginnings to the End of the Byzantine Age. Leiden – Boston: Brill 2020. - Wöckener-Gade, Eva (The Byzantine Review, 2021)
Franco Montanari (Hrsg.), History of Ancient Greek Scholarship. From the Beginnings to the End of the Byzantine Age. Leiden – Boston: Brill, 2020. viii, 709 S. – ISBN: 978-90-04-42740-2 (€ 75.00)